Roles of gap junctions, connexins, and pannexins in epilepsy - Mylvaganam, Shanthini; Ramani, Meera; Krawczyk, Michal; Carlen, Peter L. (Frontiers in Physiology, 2014)
Enhanced gap junctional communication (GJC) between neurons is considered a major factor underlying the neuronal synchrony driving seizure activity. In addition, the hippocampal sharp wave ripple complexes, associated with learning and seizures, are diminished by GJC blocking agents. Although gap junctional blocking drugs inhibit experimental seizures, they all have other nonspecific actions. Besides interneuronal GJC between dendrites, inter-axonal and inter-glial GJC is also considered important for seizure generation. Interestingly, in most studies of cerebral tissue from animal seizure models and from human patients with epilepsy, there is up-regulation of glial, but not neuronal gap junctional mRNA and protein. Significant changes in the expression and post-translational modification of the astrocytic connexin Cx43, and Panx1 were observed in an in vitro Co++ seizure model, further supporting a role for glia in seizure-genesis, although the reasons for this remain unclear. Further suggesting an involvement of astrocytic GJC in epilepsy, is the fact that the expression of astrocytic Cx mRNAs (Cxs 30 and 43) is several fold higher than that of neuronal Cx mRNAs (Cxs 36 and 45), and the number of glial cells outnumber neuronal cells in mammalian hippocampal and cortical tissue. Pannexin expression is also increased in both animal and human epileptic tissues. Specific Cx43 mimetic peptides, Gap 27 and SLS, inhibit the docking of astrocytic connexin Cx43 proteins from forming intercellular gap junctions, diminishing spontaneous seizures. Besides GJs, Cx membrane hemichannels in glia and Panx membrane channels in neurons and glia are also inhibited by gap junctional pharmacological blockers. Although there is no doubt that connexin-based gap junctions and hemichannels, and pannexin-based membrane channels are related to epilepsy, the specific details of how they are involved and how we can modulate their function for therapeutic purposes remain to be elucidated.